Math, asked by vpvgbvm, 4 months ago

Please answer my question

Simplify the following:

i) 12x + 15 y – 13 z + 4 + ( 12 – 7x + 3z – 10 y )

ii) 16x3 + 12 x2 – 9x + 18 – ( 8 + 6x3 – 2x2 + x )​

Answers

Answered by nishitakishore
1

Answer:

(i) 12x + 15y - 13z + 4 + (12 - 7x + 3z - 10y)

=> 12x + 15y - 13z + 4 + 12 - 7x + 3z - 10y

=> 12x - 7x + 15y - 10 -13z +3z + 4 + 12

=> 5x + 5y - 10z + 16

(ii) 16x3 + 12x2 - 9x + 18 - (8 + 6x3 - 2x2 + x)

=> 48 + 24 - 9x + 18 - 8 - 18 + 4 - x

=> 68 - 10x

Similar questions